Modulation of axon excitable domains by astrocytes and microglia - Garrido, Juan José (Frontiers in Cellular Neuroscience, 2026)
Neuronal communication depends on neuronal polarity and the integrity of axonal excitable domains, including the axon initial segment (AIS), nodes of Ranvier, and presynaptic terminals. In addition to the influence of neuronal input on their function and plasticity, recent evidence suggests that glial cells play a significant role in regulating these domains under both physiological and pathological conditions. In this context, this review focusses on the roles of astrocytes and microglia in the physiological modulation of the AIS and nodes of Ranvier and how these glial cells are involved in several pathological contexts, beyond its participation in the tripartite synapse. The AIS and nodes of Ranvier are not only essential for the initiation and propagation of neuronal signals but also serve as key sites of interaction with astrocytes and microglia. These interactions are crucial for maintaining neuronal excitability and overall neural circuit health. Disruptions in the interactions between glial cells and the AIS or nodes of Ranvier—whether caused by injury or disease—can profoundly affect central nervous system (CNS) function, emphasizing the importance of this dynamic relationship in both normal and pathological contexts. Recent studies have highlighted the roles of astrocytes and microglia in contacting the AIS and nodes of Ranvier, contributing to their structural plasticity, as well as in maintaining their homeostasis through the secretion of signaling factors and the regulation of ion concentrations in their microenvironment. However, the mechanisms underlying these regulatory processes remain largely unknown, and further research is required to elucidate how these interactions influence axonal physiology and contribute to axonal pathology.